The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.5216/pat.v41i2.8807
|View full text |Cite
|
Sign up to set email alerts
|

Manejo De Plantas Daninhas Em Soja Geneticamente Modificada Tolerante Ao Glyphosate

Abstract: O glyphosate possui amplo espectro de ação de plantas daninhas, porém, o uso exclusivo deste herbicida, em áreas de soja geneticamente modificada (transgênica), pode apresentar limitações. Algumas ABSTRACT RESUMOespécies podem requerer doses mais elevadas de glyphosate, aplicação sequencial ou, ainda, a adição de outro herbicida, para controle adequado (Ateh & harvey 1999). Além disto, o uso contínuo de herbicidas com o mesmo mecanismo de ação pode aumentar a pressão de seleção de biótipos de plantas daninhas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
(8 reference statements)
1
3
0
3
Order By: Relevance
“…When palisade grass was cultivated alone, from April 2010 to November 2010, a reduction of the weed diversity was observed, according to the indices of Simpson and Shannon-Weiner (Table 2). Our results corroborate those obtained by Correia et al (2011), who concluded that grass straw can reduce the establishment of some weed species in the area.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…When palisade grass was cultivated alone, from April 2010 to November 2010, a reduction of the weed diversity was observed, according to the indices of Simpson and Shannon-Weiner (Table 2). Our results corroborate those obtained by Correia et al (2011), who concluded that grass straw can reduce the establishment of some weed species in the area.…”
Section: Resultssupporting
confidence: 92%
“…Systems like these may have potential to keep weed population below the economic damage level because of the control during the grasses development, characterizing a strategy of reducing but not eradicating weeds (Noce et al, 2008;Fontes et al, 2019). Correia et al (2011) described the effects of soil coverage by palisade grass on weed control, which contributes both to the reduction of chemical application and to the control of herbicide-resistant species, such as Digitaria spp. resistant to glyphosate.…”
Section: Introductionmentioning
confidence: 99%
“…The fallow treatment had the greatest number of viable seeds in the soil. According to Correia, Durigan and Espanhol (2011), allowing the development of spontaneous species during autumn/winter is responsible for the increase in the soil seed bank. Uncovered soil facilitates the ingress of weed diaspores, boosting infestation by the seeds of this type of plant, a process that is hampered by covering the area (SILVA; DIAS-FILHO, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Palisade grass is another option that can be grown in the short-season to cut weed infestations (BRAZ et al, 2006). Correia, Durigan and Espanhol (2011) reported the positive effect of using palisade grass residues to control weeds in succession cropping, mainly under no-tillage, in addition to chemical control. Another forage crop widely used in integrated systems is Congo grass, described by Adegas, Voll and Gazziero (2011) as an efficient competitor with weed species.…”
Section: Introductionmentioning
confidence: 99%
“…Por este motivo, é fundamental proceder ao controle das plantas voluntárias de milho na cultura da soja, sendo o método químico o mais utilizado, em função de características como facilidade e rápida execução, além de apresentar elevada eficácia (Correia et al, 2011). Dúvidas com relação ao estádio de aplicação mais apropriado, bem como mecanismos de ação de herbicidas que irão apresentar eficácia no controle de plantas voluntárias de milho, ainda existem, apesar de pesquisas já terem sido desenvolvidas com esse propósito (Costa et al, 2014;Petter et al, 2015;López-Ovejero et al, 2016).…”
unclassified